MEDIA SOSIAL DAN PENYAKIT ‘AIN: PANDANGAN GENERASI Z SERTA KAITANNYA DENGAN TEORI PSIKOSOMATIK - Khairunissa; Hasanah, Noor (UIN ANTASARI BANJARMASIN, 2024)
The ease of communication on social media allows people to share photos or videos as a form of interaction, entertainment, or personal branding. However, these posts can have both positive and negative impacts, depending on the audience's reaction. One of the negative impacts that need to be watched out for is ‘ain disease, which is a condition that arises from envious or admiring looks without including prayers for blessings to Allah (SWT). This study aims to uncover Generation Z's views on the role of social media in triggering ‘ain disease while distinguishing it from psychosomatic disorders. Using a qualitative approach, the data shows that Generation Z generally believes that ‘ain can be triggered by activities on social media. However, the majority of respondents stated that not all negative views cause ‘ain; it can also be caused by psychosomatic factors. Generation Z emphasizes the importance of taking care of themselves through prayer and remembrance as protection from the adverse effects that may arise. This finding underscores the need for education to understand ‘ain proportionally so that it does not become an excuse for every bad event and to prioritize preventive measures based on spiritual values.